Identification of hypertensive patients with dominant affective temperaments might improve the psychopathological and cardiovascular risk stratification: a pilot, case–control study. Issue 1 (December 2015) - László, Andrea; Babos, Levente; Kis-Igari, Zsóka; Pálfy, Adrienn; Torzsa, Péter; Eőry, Ajándék; Kalabay, László; Gonda, Xenia; Rihmer, Zoltán; Cseprekál, Orsolya; Tislér, András; Hodrea, Judit; et al.
Abstract Background Although mood disorders and cardiovascular diseases have widely studied psychosomatic connections, data concerning the influence of the psychopathologically important affective temperaments in hypertension are scarce. To define a possibly higher cardiovascular risk subpopulation we investigated in well-treated hypertensive patients with dominant affective temperaments (DOM) and in well-treated hypertensive patients without dominant temperaments the level of depression and anxiety, arterial stiffness and serum Brain-derived Neurotrophic Factor (seBDNF). Methods 175 hypertensive patients, free of the history of psychiatric diseases, completed the TEMPS-A, Beck Depression Inventory and Hamilton Anxiety Scale questionnaires in two primary care practices. Of those 175 patients, 24 DOM patients and 24 hypertensive controls (matched in age, sex and the presence of diabetes) were selected for measurements of arterial stiffness and seBDNF level. Results Beck and Hamilton scores in DOM patients were higher compared with controls. Pulse wave velocity and augmentation index did not differ between the groups while in the DOM patients decreased brachial systolic and diastolic and central diastolic blood pressures were found compared with controls. SeBDNF was lower in the DOM group than in the controls (22.4 ± 7.2 vs. 27.3 ± 7.8 ng/mL, p  < 0.05). Conclusions Although similar arterial stiffness parameters were found in DOM patients, their increased depression and anxiety scores, the decreased brachial and central diastolic blood pressures as well as the decreased seBDNF might refer to their higher vulnerability regarding the development not only of major mood disorders, but also of cardiovascular complications. These data suggest that the evaluation of affective temperaments should get more attention both with regard to psychopathology and cardiovascular health management.